2018
DOI: 10.1111/joor.12610
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a training programme on detection of temporomandibular joint osseous changes applying pre‐defined 2D multiplane cone beam computed tomography reconstructions

Abstract: The present educational programme could be a helpful material on recognising possible osseous changes of TMJ and it can be used as a part of a training programme for GDP and for specialist candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
(37 reference statements)
1
5
0
Order By: Relevance
“…Perhaps, it was being confused with other condylar changes in form. A similar situation occurred in the previous 2D training programme 18 …”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Perhaps, it was being confused with other condylar changes in form. A similar situation occurred in the previous 2D training programme 18 …”
Section: Discussionsupporting
confidence: 74%
“…Since the criteria are valid and reliable tool and are accepted internationally, therefore, it could help to provide knowledge in a standardised way. Hellen‐Halme et al 20 and our research team in the previous study 18 reported the usefulness of using Ahmad et al 8 criteria. Both teams assumed that it could increase the diagnostic outcome among observers for magnetic resonance imaging (MRI) and CBCT evaluations of the TMJ, respectively.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Different appearances of CCAA were also presented to increase awareness of different characteristics of calcifications in the area of the carotid arteries . Similar to our results, other studies of short training programmes on specific types of diagnostic imaging have reported improvements in diagnostic accuracy for GDPs, physicians and complete novices . The GDPs in the present study also presented high skill retention at the 1‐year follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…The study did not include a long‐term follow‐up . Short training programmes including practical training have been shown to be effective to increased accuracy in diagnostic imaging among GDPs assessing osseous changes in the tempomandibular joint on Cone Beam Computer Tomography and among dental students assessing osteoporosis in dental radiographs . Similar results have also been reported for physicians when assessing pneumonia on chest radiographs and novices trained in doppler assessments of the intima thickness of the carotid artery .…”
Section: Introductionmentioning
confidence: 99%